(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
The consumption of energy drinks among adolescents has become a significant public health concern in recent years, as the high content of caffeine and other stimulants may negatively affect sleep, psychoemotional state, and academic performance. This article examines the impact of energy drink consumption on sleep and the psychoemotional state of adolescents. Particular attention is paid to the composition of energy drinks, including caffeine, taurine, and sugar, as well as their effects on the central nervous system. Changes in sleep duration and quality, levels of anxiety, irritability, and emotional instability in adolescents who regularly consume energy drinks are analyzed. The paper summarizes data from contemporary scientific studies and emphasizes the risk of developing sleep disturbances and psychoemotional disorders associated with the systematic consumption of these beverages. The study concludes that it is necessary to inform adolescents, parents, and educators about the potential negative consequences of energy drink consumption and the importance of preventive measures. Social-analytical and hygienic-statistical observational methods were used to study consumption habits, sleep indicators, psychoemotional status, and the level of adolescents’ awareness of health risks. The obtained data make it possible to develop scientifically grounded hygienic recommendations aimed at reducing energy drink consumption and preventing sleep disorders, thereby contributing to improved health and academic performance among adolescents.